Continuously tuneable acoustic metasurface for high order transmitted acoustic vortices. (23rd September 2022) - Gong, Kemeng; Zhou, Xin; Mo, Jiliang
Abstract: Existed tuneable acoustic metasurfaces (AMSs) can only transfer high order orbital angular momentum by converting the incident wave into reflected acoustic vortices (AVs). Here, a continuously tuneable AMS is designed and fabricated to produce transmitted AVs with multiple orders. The proposed AMS is composed of multiple layers of reconfigurable sector-shaped resonator-based units. A new design mechanism of the tuneable AMS is proposed to ensure that the discrete precision of the phase shift is not affected by the number of the layer. The theoretical, numerical and experimental results prove that the proposed AMS is able to continuously generate high-order transmitted AVs, which is promising in applications of real-time acoustic rotational manipulations such as acoustic microfluidics, cell manipulation, acoustic tweezers and acoustic communication.